3(3x-2)-5x=x-3

Simple and best practice solution for 3(3x-2)-5x=x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-2)-5x=x-3 equation:


Simplifying
3(3x + -2) + -5x = x + -3

Reorder the terms:
3(-2 + 3x) + -5x = x + -3
(-2 * 3 + 3x * 3) + -5x = x + -3
(-6 + 9x) + -5x = x + -3

Combine like terms: 9x + -5x = 4x
-6 + 4x = x + -3

Reorder the terms:
-6 + 4x = -3 + x

Solving
-6 + 4x = -3 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-6 + 4x + -1x = -3 + x + -1x

Combine like terms: 4x + -1x = 3x
-6 + 3x = -3 + x + -1x

Combine like terms: x + -1x = 0
-6 + 3x = -3 + 0
-6 + 3x = -3

Add '6' to each side of the equation.
-6 + 6 + 3x = -3 + 6

Combine like terms: -6 + 6 = 0
0 + 3x = -3 + 6
3x = -3 + 6

Combine like terms: -3 + 6 = 3
3x = 3

Divide each side by '3'.
x = 1

Simplifying
x = 1

See similar equations:

| 0.10+0.05(52-x)=450 | | (X+2)7=40 | | 6y+1=3x+1 | | 28w-12=16w-30 | | 3r^2-2r-3=0 | | 6x-16=4x+30 | | x^2-5xy+6y^2=0 | | (7x-2)(-5x+6)= | | a^2+14a-99=0 | | -2m-5m=9m-12 | | 7n+1=2n-4 | | -x+19+3x+19=4 | | 50+2x=120-5x | | 24+8=24+2x | | 7y-4=-14 | | u(u^4-13u^2+36)=0 | | 11+m=m-.25 | | x+1=12+3x | | u(u^4-13u^2+63)=0 | | 8a-5a=3a | | 24+2x=24+8 | | 13.4=8.5-x | | -12x+3(x-5)=6-2x | | 24+8x=24+2 | | 2(n+1)+2=3n-4 | | 8x^2-2xy+7y^2=4 | | 5p-55=a | | c=1.50+0.75h | | 11+5y=2y+8 | | 32x-7=19x-7 | | x^2-xy-6y^2=0 | | 10y^2-12y+7=0 |

Equations solver categories